Are central banks in CEE countries concerned about the burden of public debt? - Joanna Mackiewicz-Łyziak (Comparative Economic Research. Central and Eastern Europe, 2017)
The aim of this study is to analyze the monetary policy rules in the Czech Republic, Hungary and Poland, with public debt as an additional explanatory variable. We estimate linear rules by the GMM estimation and non-linear rules, using the Markov-switching model. Our findings suggest that in the Czech Republic and Poland the monetary authorities respond to growing public debt by lowering interest rates, while in Hungary the opposite may be observed. Moreover, we distinguish between passive and active monetary policy regimes and find that the degree of interest rate smoothing is lower and the response of the central banks to inflation and/or output gap is stronger in an active regime. In the passive regime, the output gap seems to be statistically insignificant.
Keywords: 330; monetary policy; general government debt; Taylor rule; regime switching